Politologia wobec feminizmu a feminizm wobec politologii - Kołodziejczak, Małgorzata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The paper discusses the issue of the complex relationship between political science as a branch of academia and modern trends in feminism, understood as a collection of mutually related ideologies. The author emphasizes that both science and ideology are forms of politi- cal practice exercised in the same social and political reality. However, they are fundamen- tally different with respect to the hierarchy of their functions. The ‘clash’ of these two products of human activity produces political science on women and the politological analy- sis of feminism (subjected first and foremost to the scientific function) on the one hand, and various proposals of feminist modifications of political science that produce feministically re- formed political science and gynocentric political science (where the scientific function is subjected to social objectives) on the other.
Political Science on Feminism versus Feminism on Political Science
Keywords: politologia; feminizm